From "some butter" to "a butter": An investigation of mass and count representation and processing - Fieder, N.; Nickels, L.; Biedermann, Britta-Andrea; Best, W. (Routledge, 2014)
This paper investigates the representation of mass and count nouns at the lexical-syntactic level, an issue that has not been addressed to date in psycholinguistic theories. A single case study is reported of a man with aphasia, R.A.P., who showed a countability specific deficit that affected processing of mass noun grammar. R.A.P. frequently substituted mass noun determiners (e.g., some, much) with count noun determiners (e.g., a, many). Experimental investigations determined that R.A.P. had a modality-neutral lexical-syntactic impairment.Furthermore, a series of novel experiments revealed that R.A.P.'s processing of mass noun determiners varied depending on how mass nouns were depicted (single vs. multiple depictions) and how congruent these were with the conceptual-semantic information of target determiners (e.g., "some" corresponds to MULTIPLE but not SINGLE concepts). R.A.P.'s determiner difficulties emerged only when mass nouns and determiners were number incongruent. The results of this research clearly indicate that nouns are lexical-syntactically specified for countability, but that the derivation of countability can additionally be influenced by conceptual-semantics. © 2014 Taylor & Francis.